Vivendo no front : discursos acionados por sujeitos na fronteira entre perspectivas LGBTs e evangélicas - Vanrochris Helbert Vieira (2015)
How the subjects on the border between LGBT (Lesbian, Gay, Bisexual and Transgender) and protestant perspectives about sexuality get along with the contradictions between them in order to make sense to their experiences and subjectivities? By using a multilocal ethnography, four groups of Belo Horizonte have been investigated in order to find subjects in this situation: the Centro de Luta pela Livre Orientação Sexual de Minas Gerais (Cellos), the Metropolitan Community Church (MCC), the Igreja Cristã Contemporânea (ICC) and the Igreja Batista da Lagoinha (IBL). The analyzed subjects are gay protestants, from inclusive churches or not, been some of them LGBT militants. The evoked discourses in IBL revolve around a “welcome” to subjects with deviant sexual experiences in relation to heteronormativity, with the intention of promoting a “healing” of them. The present discourses in ICC tell of a regulation of homossexualities and transexualilities in order to suit them for a similar standard to the nuclear traditional family, been the removal of this standard related to the “world”, that would be in opposition to “church”. The discourses circulating MCC point a refuse of a standardization of sexual experiences in order to search a distance of “religious fundamentalism” and a defense of the “Human Rights”. The found discourses in Cellos indicate a defense of a “secular State”, which would being threatened by “protestant stand” in Chamber of Deputies. In order to dialogue with the native theories, I bring theoretical discussions about heteronormativity (Prado; Junqueira), interaction (Mead), conflict (Simmel), definition of the situation (Thomas), social discourses (Bakhtin) and power (Foucault). During the fieldwork, I also have performed forays into other sixteen churches and groups of LGBT militancy.